FILOLOGICZNA PRACA LICENCJACKA A ROZWÓJ KOMPETENCJI NAUKOWYCH STUDENTA - Lankiewicz, Hadrian (Neofilolog, 2019)
The completion of undergraduate L2 studies traditionally entails preparation of a BA dissertation on a selected topic. Since Polish ministerial regulations allow interpretations, the academic community has been electrified by the possibility of alternative solutions. The ensuing discussions result in emerging proposals to substitute the traditional paper with an essay form, or with total resignation from the written part in favor of a viva. This article considers the problem with regard to the idea of key competences for lifelong learning, as defined by The European Commission, which highlight the need for practicality. Analysis of the process of writing a dissertation and its evaluation helps to draw conclusions for possible improvements.